Antibacterial, DFT and molecular docking studies of metformin complex as active material for the fabrication of copper (II) selective potentiometric sensor. (15th May 2019) - Frag, Eman Yossri; Mohamed, Marwa E.; Mohamed, Gehad G.; Fahim, Elham M.
Abstract : The prepared and characterized metformin ‐copper (II) complex was used as elecroactive material for modification of a new sensitive and selective modified carbon paste electrode (MCPE) for the potentiometric determination of copper (II) in water samples. The performance characteristics of MCPE were carried out. The electrode showed perfect potentiometric response for Cu (II) over concentration range of 1.0 × 10 −6 – 5.0 × 10 −2  mol L −1 with a detection limit of 1.0 × 10 −6  mol L −1 with divalent slope value 30.8 ± 0.92 mV decade −1 over the pH range of 2–6 and exhibits fast response time of 9 s. Also, this electrode exhibited good selectivity towards Cu (II) ions with respect to other metal ions. The obtained results using the proposed electrode were in a good agreement with those obtained using the inductively coupled plasma (ICP) method. Abstract : Application of the prepared and fully characterized copper complex in modification of carbon paste electrode for Potentiometric determination of copper ions in water samplesOptimized geometry and molecular graphs of (a) metformin and (b) metformin‐Cu(II) complex.Docking results of (a) metformin and (b) its copper complex.